Religion and conflict in modern South Asia - Gould, William, 1973- (New York : Cambridge University Press, 2012)
"This is an incisive analysis of religious conflict in South Asia, which, the author contends, arises out of the weakness of political and state structures rather than the clash of civilizations"--Provided by publisher.
"Religion and Conflict in Modern South Asia is one of the first single-author comparisons of different South Asian states around the theme of religious conflict. Based on new research and syntheses of the literature on "communalism",̥ it argues that religious conflict in this region in the modern period was never simply based on sectarian or theological differences or the clash of civilizations. Instead, the book proposes that the connection between religious radicalism and everyday violence relates to the actual (and perceived) weaknesses of political and state structures. For some, religious and ethnic mobilisation has provided a means of protest, where representative institutions failed. For others, it became a method of dealing with an uncertain political and economic future. For many it has no concrete or deliberate function, but has effectively upheld social stability, paternalism and local power, in the face of globalisation and the growing aspirations of the region's most underprivileged citizens"--Provided by publisher.
1. Introduction : community and conflict in South Asia -- 2. Building spheres of community : 1860s-1910s -- 3. Transforming spheres of community : the post-First World War colonial world -- 4. Defining spheres of community : society, religious mobilisation and anti-colonialism -- 5. State transformation, democracy and conflict : high politics and the everyday in the 1940s -- 6. Forging national consensus and containing pluralism : South Asian states between 1947 and 1967 -- 7. New conflicts and old rivalries : the 1970s and 1980s -- 8. The resurgence of communalism? : 1990 to the 2000s.
Includes bibliographical references and index.
Description based on print version record.
Keywords: South Asia -- Religion; Social conflict -- South Asia -- History; Social conflict -- Religious aspects -- History; HISTORY / Asia / India & South Asia; SOCIAL SCIENCE / Sociology of Religion; Electronic books